Membaca Puisi Mu’allaqah Zuhaer bin Abi Sulma dalam Kerangka Kekinian - Merry Choironi (Alfaz (Arabic Literatures for Academic Zealots), 2015)
Zohair bin Abi Sulma was one of the most prominent ancient Arabic poets who received his competency by both nature and culture. By nature, he lived amongst poets’ family: his father and his two sisters were poets, and so was his father’s uncle, Busyâmah from whom he learned poetry making by culture. He casted his Odes, which is to be studied here, to two persons, Harum bin Sinân and Hârits bin Auf who had efforts to make reconciliation between tribes of ʻAbas and Dzubyân, by bearing the whole fines imposed for victims from both sides. This writing tries to grasp meanings contained within the Ode by inquiry upon the common lessons and opinions traced therein. In analysis, the writer employs the theory of Ricouer in Hermeneutics. Two steps of interpretation to conduct are: initial interpretation to the extents that the text may cover and further interpretation in regard with the contexts.